Computational modeling of fracture in polymer nanocomposites undergoing large deformations via the graded-interphase-enhanced phase-field fracture approach - Kumar, Paras; Mergheim, Julia (Proceedings in Applied Mathematics and Mechanics, 2023)
“The phenomenon of fracture in polymer composites, polymer nano-composites in particular, entails a multitude of intricate mechanisms including branching and merging of several cracks along with particle debonding and subsequent plastic void growth. This work involves an extension of the standard phase-field fracture approach by means of the graded interphase concept in order to facilitate the modeling of a wide-spectrum of fracture responses, which can be observed in experimental studies concerning the fracture behavior of polymer nano-composites. Herein, motivated by the microstructure morphology of polymer nano-composites, a continuous grading of the elastic and fracture properties is considered within a finite thickness interphase region around the filler particles. Appropriate tuning of the graded-interphase model parameters enables to capture a variety of fracture responses, including cohesive failure between the filler particle and the matrix, as demonstrated via the presented numerical examples, which focus on polymer nano- composites undergoing large deformations prior to fracture.”